Astrocyte regulation of behavioral outputs: the versatile roles of calcium - Imrie, Gillian; Farhy-Tselnicker, Isabella (Frontiers in Cellular Neuroscience, 2025)
Behavior arises from coordinated brain-wide neural and glial networks, enabling organisms to perceive, interpret, and respond to stimuli. Astrocytes play an important role in shaping behavioral output, yet the underlying molecular mechanisms are not fully understood. Astrocytes respond to intrinsic and extrinsic cues with calcium (Ca2+) fluctuations, which are highly heterogeneous across spatio-temporal scales, contexts, and brain regions. This heterogeneity allows astrocytes to exert dynamic regulatory effects on neuronal function but has made it challenging to understand the precise mechanisms and pathways linking astrocytic Ca2+ to specific behavioral outcomes, and the functional relevance of these signals remains unclear. Here, we review recent literature uncovering roles for astrocytic Ca2+ signaling in a wide array of behaviors, including cognitive, homeostatic, and affective focusing on its physiological roles, and potential pathological implications. We specifically highlight how different types of astrocytic Ca2+ signals are linked to distinct behavioral outcomes and discuss limitations and unanswered questions that remain to be addressed.